Sram v doživljanju pacienta in terapevta - Kramar, Metka (Psihološka obzorja (Ljubljana), 2010)
Bulimia, as well as other eating disorders, is largely a disorder of shame. The three presented patients are typically experiencing themselves as worthless, disgusting human creatures, helplessly entrapped in the addiction. A model of psychotherapeutic approach to shame according to Kaufman (1989) is demonstrated. In order to help such a patient to resolve feelings of shame and overcome addiction, psychotherapist should know how his or her own shame manifests, what he or she experineces it, which events activate shame and also his or her specific responses to shame.
Keywords: bulimija; sram; psihoterapija